2016
DOI: 10.1016/j.cortex.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale functional network reorganization in 22q11.2 deletion syndrome revealed by modularity analysis

Abstract: The 22q11.2 deletion syndrome (22q11DS) is associated with cognitive impairments and a 41% risk of developing schizophrenia. While several studies performed on patients with 22q11DS showed the presence of abnormal functional connectivity in this syndrome, how these alterations affect large-scale network organization is still unknown. Here we performed a network modularity analysis on whole-brain functional connectomes derived from the resting-state fMRI of 40 patients with 22q11DS and 41 healthy control partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 91 publications
(119 reference statements)
5
12
0
Order By: Relevance
“…The pattern of altered couplings in 22q11DS was characterized by predominantly longer anti-couplings, accounting for more than half (13/25) of the alterations. Longer anti-coupling is suggestive of increased segregation between brain networks and is in agreement with evidence of increased segregation and decreased integration of structural and functional brain networks in both 22q11DS and non-syndromic psychosis (64,76,77,79,91,93). Network segregation is a central feature of brain function that is important for cognition and attention (97) and its alterations in 22q11DS may be reflective of cognitive disabilities on a more global level than the above mentioned alterations in triple network activation that concentrates on three core networks.…”
Section: Alterations In 22q11ds: Implication Of Cognitive and Emotionsupporting
confidence: 80%
“…The pattern of altered couplings in 22q11DS was characterized by predominantly longer anti-couplings, accounting for more than half (13/25) of the alterations. Longer anti-coupling is suggestive of increased segregation between brain networks and is in agreement with evidence of increased segregation and decreased integration of structural and functional brain networks in both 22q11DS and non-syndromic psychosis (64,76,77,79,91,93). Network segregation is a central feature of brain function that is important for cognition and attention (97) and its alterations in 22q11DS may be reflective of cognitive disabilities on a more global level than the above mentioned alterations in triple network activation that concentrates on three core networks.…”
Section: Alterations In 22q11ds: Implication Of Cognitive and Emotionsupporting
confidence: 80%
“…default mode, attention) that show varying degrees of disruption in schizophrenia (6). Observed modularity values for the hippocampal network were lower than those typically seen when modularity is optimized across multiple networks (48; 76; 77). The signals of nodes in a single network are expected to be comparatively similar, thus producing lower estimates of within-network modularity.…”
Section: Discussionmentioning
confidence: 62%
“…Recent findings have shown substantially decreased modularity across cortical networks in schizophrenia (6; 47). Additionally, abnormal modularity has been noted in genetic models of schizophrenia (48), suggesting the network dysfunction may be a core feature of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…However, no study to date directly investigated connectivity between the three networks in patients with 22q11DS. Nevertheless, in a recent study from our group [Scariati et al, 2016a], we reported altered connectivity of the ACC with the DMN and the DLPFC, as well as impaired maturation of the DLPFC connectivity with age. Furthermore, two studies using resting-state electroencephalography (EEG) suggested that the shifting between CEN and SN activation is impaired in 22q11DS [Tomescu et al, 2014[Tomescu et al, , 2015.…”
Section: Introductionmentioning
confidence: 61%